2016
DOI: 10.1113/jp272864
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channels in the heart: structure, function and regulation

Abstract: This paper is the outcome of the fourth UC Davis Systems Approach to Understanding Cardiac Excitation-Contraction Coupling and Arrhythmias Symposium, a biannual event that aims to bring together leading experts in subfields of cardiovascular biomedicine to focus on topics of importance to the field. The theme of the 2016 symposium was 'K Channels and Regulation'. Experts in the field contributed their experimental and mathematical modelling perspectives and discussed emerging questions, controversies and chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 162 publications
(301 reference statements)
1
82
1
Order By: Relevance
“…The electrical activity of the heart is an extraordinary arrangement by multiple categories of ion channels, and the movement of ions across the cytoplasmic membrane of cardiomyocytes is controlled by transmembrane proteins [32]. The membrane potential and the rate of membrane repolarization are managed by potassium (K + ) channels [33]. Among these channels, I K1 is a strong inward rectifier K + -selective current, which plays important roles in modulating the RMP and the final repolarization phase of action potential in cardiomyocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…The electrical activity of the heart is an extraordinary arrangement by multiple categories of ion channels, and the movement of ions across the cytoplasmic membrane of cardiomyocytes is controlled by transmembrane proteins [32]. The membrane potential and the rate of membrane repolarization are managed by potassium (K + ) channels [33]. Among these channels, I K1 is a strong inward rectifier K + -selective current, which plays important roles in modulating the RMP and the final repolarization phase of action potential in cardiomyocytes [34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that drugs with similar binding affinity but different binding kinetics can have diverse effects[3, 149, 150]. The most commonly used metric for drug blockade is IC 50 , but it provides an average measure of drug potency to supress ion currents without any mechanistic insights.…”
Section: Towards Md-based Kinetic Models For Ion Channels Gatingmentioning
confidence: 99%
“…Unsurprisingly, ion channels have been among the most common drug targets for decades of treatment efforts and novel drug development. While many ion channel targets are known (for example pace-maker channels: HCNs), the development of drugs that act as highly ion channel specific modulators remains challenging[3]. High-throughput technologies, animal models, detailed biochemical and biophysical explorations are all dispatched to identify potential leads with high specificity to a transmembrane protein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations